Using CONTAM to design ventilation strategy of negative pressure isolation ward considering different height of door gaps - Mingyao Ma; Changsheng Cao; Yukun Xu; Zhijian Liu; Lingjie Zeng; Chengquan Zhang; Jun Gao (Energy and Built Environment, 2024)
Infectious disease departments in hospitals require pressure gradient to create unidirectional airflow to prevent the spread of contaminants, typically by creating active air infiltration through the difference between supply and exhaust air volumes. The door gap is the channel of air flow between rooms, so its height has an important influence on the pressure difference and infiltration air volume of the room. There is still a lack of research on setting reasonable ventilation strategies according to the different heights of door gaps at different positions in the building. In this study, model of a set of isolation wards was established and analyzed using the multi-zone simulation software CONTAM, and the ventilation strategies with different heights of door gaps were applied to the actual infection diseases department. The results show that in a building with ventilation system divided by functional area, the difference in the height of the door gaps requires different active infiltration air volumes. Pressure fluctuations in the medical and patient corridors are greater than in other rooms. The significance of this study is to understand the active infiltration of air to guide the design and operation of ventilation systems in infectious disease hospitals or building remodeled to isolate close contacts of COVID-19 patients. It is also instructive for the design of pressure gradients in clean workshops, biological laboratories, and other similar buildings.